Technology Entrepreneurship (ENT600) : Rollin’ Smoke BBQ Grill / Ahmad Nur Aiman Ahmad Jalani - Ahmad Jalani, Ahmad Nur Aiman; Sardon, Farhana; Faiz, Muhammad Amir; Shafik, Muhammad Najmi; Mohd Raffi, Muhammad Salman (2021)
This is an endeavour to grasp how the theories can be applied to a practical situation. As a student in UiTM Perlis, it is a part of study for everyone to undergo a new product development project. So, for this purpose, we got the chance to develop and innovate a product that deeply interests us, which is a barbeque grill. In the first phase of the report, there was a general introduction to the new product development. In this part, the problem faced by users when they are barbequing, analysis for methodology, and limitation were explained. In the next phase of the report, the definition, classification, and process of new product development were explained thoroughly. The classification of the new product is explained through its improvements and revisions of the product. Furthermore, the process of new product development can be classified into five processes which are research and development, product design/features, concept testing, prototype, and test marketing. Concept screening and concept generation were discussed in the research and development section. In addition, the concept testing and market survey testing was developed in questionnaires and has been distributed to 20 respondents using Google Form. Last but not least, in test marketing, a few techniques were used to make this product accepted by consumers, such as customers’ experience, opinions, and feedback regarding the new product. In conclusion, the feedback received from respondents was very helpful in order for us to fill up the requirement of consumer.